MEDIASI LATIHAN ANGKAT BEBAN TERHADAP PENINGKATAN EKSPRESI PGC-1α PADA REMAJA PEREMPUAN PENDERITA OBESITAS - Moh. Alfino Arisandi; Desiana Merawati; Sugiharto Sugiarto (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
Peroxisome proliferator activated receptor-gamma coactivator 1 (PGC-1α) is closely related to metabolic status in obese patients. This study aims to analyze the response of lifting weights to increased levels of PGC-1α as a metabolic status in obese people. This study was a true experimental study with the randomized pretest-posttest control group design using 14 female adolescents aged 20-25, body mass index (BMI) 25-30 kg/m2, normal systolic blood pressure, normal resting heart rate, Percentage of body fat ≥ 30%, and divided into 2 groups randomly, namely the control group without intervention 7 subjects and the group given weight training intervention 6 subjects. PGC-1α levels were examined using the Enzyme Link Immunosorbent Assay (ELISA) kit (Cat.No.:E-EL-H6017; Elabscience, Inc., USA). Data analysis techniques using SPSS version 21.0. The results of the analysis of the average pretest and posttest PGC-1α levels in K1 (1.19 ± 0.89 vs 1.27 ± 0.65 ng/mL, p = 0.746), and K2 (1.07 ± 0.26 vs 2.60 ± 0.40 ng/mL, p = 0.000). It is recommended for future research using male and female subjects, so that the results of the study can be generalized to both sexes.